Gallium Nitride Inverter Design with Compatible Snubber Circuits for Implementing Wireless Charging of Electric Vehicle Batteries - Fatemeh Rahmani; Payam Niknejad; Tanushree Agarwal; Mohammadreza Barzegaran (Machines, 2020)
High-frequency wireless power transfer (WPT) technology provides superior compatibility in the alignment with various WPT standards. However, high-efficiency and compact single-phase power switching systems with ideal snubber circuits are required for maximum power transfer capability. This research aims to develop an inverter using Gallium Nitride (GaN) power transistors, optimized RCD (resistor/capacitor/diode) snubber circuits, and gate drivers, each benefitting WPT technology by reducing the switching and conduction loss in charging electric vehicle batteries. A full-bridge GaN inverter was simulated and instituted as part of the wireless charging circuit design. The RCD circuits were adjusted by transferring maximum power from the power supply to the transmitter inductor. For verification of the simulated output, lab-scale experiments were implemented for two half-bridges controlled by gate drivers with corresponding snubber circuits. After authenticating the output results, the GaN inverter was tested with an input range of 30 V to deduce the success of charging electric vehicle batteries within an efficient time frame. The developed inverter, at 80 kHz frequency, was applied in place of a ready-to-use evaluation board, fully reducing less harmonic distortion and greatly increasing WPT system efficiency (~93%). In turn, the designed GaN inverter boasts considerable energy savings, resulting in a more cost-effective solution for manufacturers.